Mechanisms of chronic inflammation improvement by exercise: Focus on immune response of local tissue - Noriaki Kawanishi; Hiromi Yano; Tsubasa Mizokami; Katsuhiko Suzuki (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Obesity is associated with the pathogenesis of chronic inflammatory diseases, such as type II diabetes and nonalcoholic steatohepatitis, which in turn have been attributed to the chronic inflammation in visceral adipose tissue and liver. The innate immune system via macrophages, neutrophils and lymphocytes is related to development of chronic inflammation. Exercise has anti-inflammatory effects and may prevent the development of chronic inflammatory diseases. To elucidate mechanisms of chronic inflammation improvement and/or prevention in the local tissue due to exercise is important to ensure development of effective exercise therapy. This review provides information to elucidate the molecular mechanisms from the perspective of immune regulation on the improvement of chronic inflammation due to exercise.